2012
DOI: 10.2466/24.22.cp.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Spatial Separation in the Poggendorff Illusion

Abstract: This study examined the responses of 40 undergraduate women and 40 men to two Poggendorff figures, a traditional figure with the right oblique line omitted and a modified variant with the left vertical line and the right oblique line absent. Participants placed a dot on the right vertical line where the oblique line, if extended, would intersect the right vertical line. The results showed that women displayed larger illusions than men on both figures, consistent with past findings. Finding a sex difference wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Both genders were found to be equally accurate and confident in their answers. Once more this reflects on an issue that is still inconclusive and debated in the research field of optical illusion processing and visuospatial processing in general, with some studies reporting no gender performance differences (for instance, Gootjes et al 2008;Rasmjou et al 1999;Vaquero et al 2004) while others report a male behavioral dominance (for instance, Beckett 1990, Pratarelli and Steitz 1995, Miller 1999, 2001, Ninio and O'Regan 1999, Collaer and Nelson 2002Declerck and De Branbader 2002, Ling et al 2006, Knudson et al 2012. Alternatively, this discrepancy may reflect a need for behavioral indices more sensitive than those of accuracy and confidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both genders were found to be equally accurate and confident in their answers. Once more this reflects on an issue that is still inconclusive and debated in the research field of optical illusion processing and visuospatial processing in general, with some studies reporting no gender performance differences (for instance, Gootjes et al 2008;Rasmjou et al 1999;Vaquero et al 2004) while others report a male behavioral dominance (for instance, Beckett 1990, Pratarelli and Steitz 1995, Miller 1999, 2001, Ninio and O'Regan 1999, Collaer and Nelson 2002Declerck and De Branbader 2002, Ling et al 2006, Knudson et al 2012. Alternatively, this discrepancy may reflect a need for behavioral indices more sensitive than those of accuracy and confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding possible gender differences in the processing of optical illusions, most of the work has been carried out in a behavioral level of analysis. In this framework, there is converging evidence indicating that males outperform females in visual illusion processing tasks related to the Poggendorff illusion (Beckett 1990, Ninio and O'Regan 1999, Collaer and Nelson 2002, Declerck and De Branbader 2002, Ling et al 2006, Knudson et al 2012, the Ponzo illusion (Miller 1999(Miller , 2001 and other cases of optical illusions (for instance Pratarelli and Steitz 1995). It is believed that these differences reflect the fact that the two genders employ different strategies to process an optical illusion.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the effectiveness of illusions increases or decreases with age depending on the illusion mechanism [10]. In addition, it has been reported that there are some optical illusions, such as the Poggendorff illusion, in which the magnitude of the illusion is larger for females than for males [11], [12].Furthermore, it has been reported that females become less accustomed to the M üller-Lyer illusion than males when the illusion is presented repeatedly and that the illusion effect persists [13]. The occurrence of cross-modal effects has also been reported to vary depending on the age, gender, and culture of the experiencer [14].…”
Section: Introductionmentioning
confidence: 99%